2017
DOI: 10.7710/2162-3309.2150
|View full text |Cite
|
Sign up to set email alerts
|

Open data, [open] access: linking data sharing and article sharing in the Earth Sciences

Abstract: INTRODUCTIONThe norms of a research community influence practice, and norms of openness and sharing can be shaped to encourage researchers who share in one aspect of their research cycle to share in another. Different sets of mandates have evolved to require that research data be made public, but not necessarily articles resulting from that collected data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…They state, "There seems to be a stark contrast between the desire for openness of published results and the desire for openness of process and evidence." Within the context of a specific discipline, Teplitzky (2017) approached open access and data sharing from the opposite direction, looking at how many data sets in the Pangaea repository had corresponding journal articles available via open access. The author found that the incidence of publication in gold open access journals increased over time and many articles were available through more than one source.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They state, "There seems to be a stark contrast between the desire for openness of published results and the desire for openness of process and evidence." Within the context of a specific discipline, Teplitzky (2017) approached open access and data sharing from the opposite direction, looking at how many data sets in the Pangaea repository had corresponding journal articles available via open access. The author found that the incidence of publication in gold open access journals increased over time and many articles were available through more than one source.…”
Section: Literature Reviewmentioning
confidence: 99%
“…I searched the article DOI and if necessary, the article title and clicked the Easy Search Unpaywall link to see where it led. Similar to the study by Teplitzky (2017), I also looked for the articles in ResearchGate, an academic social media platform that facilitates research article sharing, whether the sharing is legal or infringes on copyright (McKenzie 2018). I searched the article title in the ResearchGate search box, and I only counted access if I could immediately download the article.…”
Section: Methodsmentioning
confidence: 99%
“…Of the limited literature linking open data and OA, a study by Teplitzky (2017) is particularly relevant. Focused on the earth sciences, Teplitzky (2017) investigated to what extent researchers who shared data via the Pangaea repository also made the related articles openly available. The percentage of articles linked to Pangaea datasets that were published in Gold/Full OA journals increased from 9.7% in 2010 to 30.9% in 2015.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…credit card transactions, activities on the web, phone calls, widespread diseases, etc. Publishing and releasing such type of data can provide benefits to researchers and decision makers, owe to their flexibility and availability of detailed information (Teplitzky 2014). For example, healthcare organizations collect and analyze medical data for the discovery of new drugs and therapies (Rider and Chawla 2013).…”
Section: Introductionmentioning
confidence: 99%